Higher Troponin Levels on Admission are associated With Persistent Cardiac Magnetic Resonance Lesions in Children Developing Myocarditis After mRNA-Based COVID-19 Vaccination. Issue 2 (31st October 2022) - Manno, Emma Concetta; Amodio, Donato; Cotugno, Nicola; Rossetti, Chiara; Giancotta, Carmela; Santilli, Veronica; Zangari, Paola; Rotulo, Gioacchino Andrea; Villani, Alberto; Giglioni, Emanuele; Turchetta, Attilio; Cafiero, Giulia; et al.
Abstract : Background: Acute pericarditis/myocarditis is a rare complication of the mRNA-based vaccines and although mostly self-limiting, long-term sequelae remain unclear. Methods: We enrolled all patients admitted to the emergency department between September 2021 and February 2022 meeting the CDC work case definition, with symptoms onset after mRNA-based COVID-19 vaccine. Alternative virologic causes were excluded. Clinical data, laboratory values, cardiologic evaluation, electrocardiogram (ECG), and echocardiogram (ECHO) were collected on admission, at discharge, and during follow-up in all patients. Cardiac Magnetic Resonance (CMR) was performed only in those with signs consistent with myocarditis. Results: We observed 13 patients (11M and 2F), median age 15 years, affected by acute pericarditis/myocarditis after COVID-19 mRNA vaccination (11 after Comirnaty® and 2 after Spikevax®). Symptoms'onset occurred at a median of 5 days (range, 1 to 41 days) after receiving mRNA vaccine (13 Prizer 2 Moderna): 4 patients (31%) after the 1st dose, 6 (46%) after the 2nd, and 3 (23%) after 3rd dose. Increased levels of high-sensitive troponin T (hsTnT) (median 519, 5 ng/mL) and N-terminal-pro hormone BNP (NT-proBNP) (median 268 pg/mL) and pathognomonic ECG and ECHO abnormalities were detected. On admission, 7 of 13 (54%) presented with myopericarditis, 3 (23%) with myocarditis, and 3 (23%) with pericarditis; CMR was performed in 5 patients upon pediatric cardiologist prescription and findings were consistent with myocarditis. At 12 weeks of follow-up, all but one patient (92%), still presenting mild pericardial effusion at ECHO, were asymptomatic with normal hsTnT and NT-proBNP levels and ECG. On CMR 6 of 9 patients showed persistent, although decreased, myocardial injury. Higher hsTnT levels on admission significantly correlated with persistent CMR lesions. Conclusion: Evidence of persistent CMR lesions highlights the need for a close and standardized follow-up for those patients who present high hsTnT levels on admission.